GENERATING IDEAS TO WRITE NARRATIVE THROUGH ILLUSTRATED POEM : INDONESIAN EFL STUDENTS’ EXPERIENCES - Nabilla, Ega Viorenti; Fithriani, Rahmah (Universitas PGRI Sumatera Barat, 2023)
Writing has become the most important skill to learn for English as a foreign language (EFL) students. However, students often have difficulty getting ideas when writing narrative stories. This article aims to offer suggestions on using pictorial poetry to generate ideas for writing narrative texts as an innovation in learning English. Pre-tests and written assignments were used for data collection in this qualitative study. Participants' narrative texts were evaluated using adaptations from the Teaching for Better Educators Model (2019) and Advanced English Books by the Ministry of Education and Culture Research and Technology (2020) Narrative Analytical Rubric. Seven students from a state senior high school in Percut Sei Tuan, Indonesia, became the participants. The results showed that participants had difficulties in getting ideas during the pre-test but were able to come up with writing ideas after being stimulated using the pictorial poem